The Burden of HIV, Hepatitis B and Hepatitis C by Armed Conflict Setting: The Nigeria AIDS Indicator and Impact Survey, 2018 - Gambo G. Aliyu; Sani H. Aliyu; Akipu Ehoche; Deepa Dongarwar; Rafeek A. Yusuf; Muktar H. Aliyu; Hamisu M. Salihu (Ubiquity Press, 2021)
Background: Against a background of security challenges, Nigeria conducted recently the largest population-based HIV survey in the world to ascertain the burden of the HIV disease in the country. Objective: We evaluated the main outcomes of the survey and the level of success using participation/response indicators. Methods: The survey was conducted from July-December 2018 by over 6,000 field staff across Nigeria in six consecutive webs, using two-stage cluster sampling. We estimated the prevalence of HIV, hepatitis B and hepatitis C in the entire country and by conflict zone status. Adjusted odds ratios (OR) and 95% confidence intervals (CI) from survey logistic regression models were used to compare the likelihood of test positivity for the three infections between zones. Findings: A total of 186,405 adults were interviewed from 97,250 households in 3,848 census enumeration areas. The overall HIV, hepatitis B and hepatitis C positivity rates were 1.55%, 7.63% and 1.73%, respectively. The prevalence of HIV, hepatitis B and C infection was significantly greater in conflict than non-conflict zones (HIV: 1.75% versus 1.0%; hepatitis B: 9.9% versus 7.3%; and hepatitis C: 3.2% versus 0.3%; p < 0.01 in all cases). Individuals living in conflict zones were about three times as likely to test positive for HIV (OR = 2.80, 95% CI = 2.08, 3.60) and nearly six times as likely to test positive for hepatitis C (OR = 5.90, 95% CI = 2.17, 16.67). Conclusion: Large population-based surveys are feasible, even in armed conflict settings. The burden of HIV, hepatitis B and hepatitis C was significantly higher in areas of conflict in Nigeria, highlighting the need for reinforced public health control measures in these settings in order to attain UNAIDS' 95-95-95 targets of controlling the HIV epidemic in sub-Saharan Africa by 2030.